A study on the effectiveness of the implementation of pest control work (termite) in building / Mohd Hisham Saat - Saat, Mohd Hisham (2003)
Pest control is a very general and large topic. This thesis is about termite controls. We are on the verge of a new era that is information technologies (IT). Our Malaysian people are equipped with so many technologies that are Internet, mobile WAP, and so much more. But sadly to say, that they do not know the importance of pest control and how do this pest affect their life, especially termite that can damage and harm their house maybe their life one-day, who know. Termite has live here on earth even before man was born. It is one of the dangerous pests that can destroy your home in the matter off year. Termite eat wood but it is on forest ground. Yes, they eat fallen logs and stumps off the forest floor. Then come development, houses and building was built left forest near extinction. This made termite turn to others food supply to live. These mean that termite turn to our property as its food. Termite can eat away the equity you have build in your home and property. According to the United States Department of Agriculture, termite infests millions of home nation-wide, causing over 750 million in damage annually…